VEGETATIVE REPRODUCTION OF MOSSES IN SOIL AROUND THE ANTARCTIC MOSS COMMUNITY (EXTENDED ABSTRACT) (14th Symposium on Polar Biology) - イムラ, サトシ; ヒグチ, マサノブ; カンダ, ヒロシ; イワツキ, ゼンノスケ; IMURA, Satoshi; HIGUCHI, Masanobu; KANDA, Hiroshi; IWATSUKI, Zennoske (National Institute of Polar Research, 1993)
P(論文) departmental bulletin paper